Additional surgical risk factors and patient characteristics for mesh erosion after abdominal sacrocolpopexy - Akyol, Alpaslan; Akca, Aysu; Ulker, Volkan; Gedikbasi, Ali; Kublay, Arzu; Han, Agahan; Numanoglu, Ceyhun (Wiley, 2014)
AimThe aim of this study is to determine the risk factors of mesh exposures following abdominal sacral colpopexy (ASC) in which polypropylene mesh is used. MethodsThis is a retrospective cohort study of patients who underwent ASC and were subsequently followed for development of mesh exposure for vaginal/vault prolapse between 2002 and 2012. Demographics and risk factors of the patients who did develop mesh exposure after ASC and the ones who did not were compared. ResultsIn 42 months of survey, 19 of the 292 patients who underwent ASC developed mesh exposure. It was found that rates of patients with stage 3-4 prolapse were significantly greater in the mesh exposure group than in the control group (P=0.04). Rates of mesh exposure were lower in patients with previous hysterectomy (P=0.03). Also, it was found that concomitant hysterectomy or three or more additional procedures increased the risk of mesh exposure (P=0.03 and P=0.02). ConclusionIn abdominal sacrocolpopexy operations in which polypropylene meshes are used, stage 3 or 4 prolapse, concomitant hysterectomy and three or more additional procedures increase the risk of mesh exposure development.
Keywords: abdominal sacrocolpopexy; hysterectomy; mesh exposure; pelvic organ prolapse; polypropylene mesh